2004
DOI: 10.1152/ajpcell.00044.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fiber type and temperature dependence of inorganic phosphate: implications for fatigue

Abstract: Debold, E. P., H. Dave, and R. H. Fitts. Fiber type and temperature dependence of inorganic phosphate: implications for fatigue. Am J Physiol Cell Physiol 287: C673-C681, 2004. First published May 5, 2004; 10.1152/ajpcell.00044.2004.-Elevated levels of P i are thought to cause a substantial proportion of the loss in muscular force and power output during fatigue from intense contractile activity. However, support for this hypothesis is based, in part, on data from skinned single fibers obtained at low temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
114
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(143 citation statements)
references
References 52 publications
(76 reference statements)
20
114
1
1
Order By: Relevance
“…Peripherally, fatiguing exercise can result in changes in the muscle tissue that includes increases in lactate, phosphate and creatinine kinase, decreases in pH, and infiltration of neutrophils. 2,8,11,30 Changes in these substances could directly activate nociceptors through acid sensing ion channels and increased release of cytokines and prostaglandins. 5,22,27,31,42,43,47 Alternatively, there could be changes in the buffering capacity of the muscle to maintain pH such that a pH of 5 is buffered slower than under nonfatigue conditions.…”
Section: Peripheral Mechanisms For Enhanced Nociception After Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Peripherally, fatiguing exercise can result in changes in the muscle tissue that includes increases in lactate, phosphate and creatinine kinase, decreases in pH, and infiltration of neutrophils. 2,8,11,30 Changes in these substances could directly activate nociceptors through acid sensing ion channels and increased release of cytokines and prostaglandins. 5,22,27,31,42,43,47 Alternatively, there could be changes in the buffering capacity of the muscle to maintain pH such that a pH of 5 is buffered slower than under nonfatigue conditions.…”
Section: Peripheral Mechanisms For Enhanced Nociception After Fatiguementioning
confidence: 99%
“…Eccentric induced soreness is generally associated with inflammatory changes in exercised muscle that includes infiltration of leukocytes, increases in lactate, increases in phosphate, fatigue, and pain. 2,8,11,30 In human subjects with experimental muscle pain, there is a decrease in muscle peak force and endurance in painful and in synergistic muscles. 7 A low-intensity, 60-minuteduration tooth clenching task produces fatigue and pain during the task, 49 suggesting fatigue produces pain.…”
mentioning
confidence: 99%
“…Increased [P i ] is thought to reduce muscle force by reversing the force-generating P i release step by mass action (Hibberd et al, 1985). According to Debold et al (rat muscle fibres), the [P i ] dependency of muscle fatigue is temperature related, with a more pronounced effect of [P i ] at low temperatures (Debold et al, 2004). For ectothermic (marine) animals such studies have, to our knowledge, not been undertaken.…”
Section: High T Cmentioning
confidence: 99%
“…10,18,95 Subsequent experiments that exposed skinned single muscle fibers to fatiguing concentrations of Pi (~30 mM) and H + (pH 6.2 to 6.5) showed that these ions dramatically reduce maximal isometric force, 15,38,61 unloaded shortening velocity, 13 and peak power, 24,46,58 providing strong evidence that these ions play a causative role in the fatigue process. More specifically, because these experiments were , and thus with a fully activated thin filament, it suggests that these depressive effects are due, in part, to a direct effect on the actomyosin crossbridge.…”
mentioning
confidence: 99%
“…23,28 In addition, parallel advancements in single muscle fiber technology and transgenic manipulation of the contractile proteins are also providing important new insights into the molecular basis of the fatigue process. 20,24,26,46,[58][59][60] Characterizing the mechanisms of fatigue at the cellular and molecular levels is important because many of the most promising therapeutic interventions act at this level to attenuate the debilitating effects of fatigue in clinical populations. 30, 51,57,74,87 In addition to directly inhibiting the crossbridge cycle, the metabolic by-products that are elevated during intense contractile activity are thought to indirectly affect contractile function by altering the ability of the muscle regulatory proteins (troponin [Tn] and tropomyosin [Tm]) to regulate actomyosin binding by making the thin filament less sensitive to Ca 2+ .…”
mentioning
confidence: 99%